Pengaruh Green Marketing, Green Brand Trust dan Green Brand Image terhadap Purchase Intention Generasi Z pada Produk Miniso di Kota Padang - Putry Amanda; Lidya Martha (ARZUSIN, 2026)
Although environmental sustainability issues have received increasing attention in consumer behavior studies, studies that specifically discuss the effectiveness of green marketing strategies in influencing Generation Z’s purchase intention in nonmetropolitan areas remain limited. This study aimed to analyze the influence of green marketing, green brand trust, and green brand image on Generation Z’s purchase intention for Miniso products in Padang City. This study used a quantitative approach with a survey design, involving 190 respondents selected using purposive sampling. Data were collected using a questionnaire and analyzed through multiple linear regression using SPSS. The results showed that green marketing had no significant effect on purchase intention, whereas green brand trust and green brand image had positive and significant effects. This finding contributes to the development of the Theory of Planned Behavior and expands understanding of consumer behavior in the context of sustainable marketing. Thus, this study affirms that trust and environmentally friendly brand image play an important role in shaping Generation Z’s purchase intention, so companies need to strengthen their environmental credibility and positioning to improve the effectiveness of sustainable marketing strategies.